The acceleration of cardiomyogenesis in embryonic stem cells in vitro by serum depletion does not increase the number of developed cardiomyocytes - Radaszkiewicz, Katarzyna Anna; Sýkorová, Dominika; Binó, Lucia; Kudová, Jana; Bébarová, Markéta; Procházková, Jiřina; Kotasová, Hana; Kubala, Lukáš; Pacherník, Jiří (PloS one, 2017)
The differentiation of pluripotent embryonic stem (ES) cells into various lineages in vitro represents an important tool for studying the mechanisms underlying mammalian embryogenesis. It is a key technique in studies evaluating the molecular mechanisms of cardiomyogenesis and heart development and also in embryotoxicology. Herein, modest modifications of the basic protocol for ES cell differentiation into cardiomyocytes were evaluated in order to increase the yield and differentiation status of developed cardiomyocytes. Primarily, the data show that ES cell cultivation in the form of non-adherent embryoid bodies (EBs) for 5 days compared to 8 days significantly improved cardiomyogenic differentiation. This is illustrated by the appearance of beating foci in the adherent EBs layer at earlier phases of differentiation from day 10 up to day 16 and by the significantly higher expression of genes characteristic of cardiomyogenic differentiation (sarcomeric alpha actinin, myosin heavy chain alpha and beta, myosin light chain 2 and 7, and transcriptional factor Nkx2.5) in EBs cultivated under non-adherent conditions for 5 days. The ratio of cardiomyocytes per other cells was also potentiated in EBs cultivated in non-adherent conditions for only 5 days followed by cultivation in adherent serum-free culture conditions. Nevertheless, the alteration in the percentage of beating foci among these two tested cultivation conditions vanished at later phases and also did not affect the total number of cardiomyocytes determined as myosin heavy chain positive cells at the end of the differentiation process on day 20. Thus, although these modifications of the conditions of ES cells differentiation may intensify cardiomyocyte differentiation, the final count of cardiomyocytes might not change. Thus, serum depletion was identified as a key factor that intensified cardiomyogenesis. Further, the treatment of EBs with N-acetylcysteine, a reactive oxygen species scavenger, did not affect the observed increase in cardiomyogenesis under serum depleted conditions. Interestingly, a mild induction of the ventricular-like phenotype of cardiomyocytes was observed in 5-day-old EBs compared to 8-day-old EBs. Overall, these findings bring crucial information on the mechanisms of ES cells differentiation into cardiomyocytes and on the establishment of efficient protocols for the cardiomyogenic differentiation of ES cells. Further, the importance of determining the absolute number of formed cardiomyocyte-like cells per seeded pluripotent cells in contrast to the simple quantification of the ratios of cells is highlighted.
Keywords: Actinin; Acetylcysteine; homeoboxový protein Nkx-2.5; acetylcystein; techniky in vitro; Myosins; Embryonic Stem Cells; aktinin; embryonální kmenové buňky; kultivované buňky; kardiomyocyty; Animals; Culture Media, Serum-Free; kultivační média bez séra; zvířata; Homeobox Protein Nkx-2.5; Myocytes, Cardiac; myši; Cells, Cultured; Mice; myosiny; In Vitro Techniques